2006
DOI: 10.1161/circulationaha.105.608679
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Progression of Peripheral Arterial Disease in Large and Small Vessels

Abstract: Background-Data on the natural history of peripheral arterial disease (PAD) are scarce and are focused primarily on clinical symptoms. Using noninvasive tests, we assessed the role of traditional and novel risk factors on PAD progression. We hypothesized that the risk factors for large-vessel PAD (LV-PAD) progression might differ from small-vessel PAD (SV-PAD). Methods and Results-Between 1990 and 1994, patients seen during the prior 10 years in our vascular laboratories were invited for a new vascular examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
189
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(209 citation statements)
references
References 79 publications
(63 reference statements)
14
189
4
2
Order By: Relevance
“…This raises the question whether it is possible that the manifestation of atherosclerosis may present differentially among individual patients’ arteries. More aggressive expression of atherosclerosis has been found in patients with distal versus aortoiliac disease and in patients in whom higher inflammation markers can be found 17, 18, 19. These studies suggested which concomitant factors could be associated with a more aggressive underlying atherosclerotic process but were unable to document whether this could be linked to the number of lower extremity lesions and patient outcomes 17, 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question whether it is possible that the manifestation of atherosclerosis may present differentially among individual patients’ arteries. More aggressive expression of atherosclerosis has been found in patients with distal versus aortoiliac disease and in patients in whom higher inflammation markers can be found 17, 18, 19. These studies suggested which concomitant factors could be associated with a more aggressive underlying atherosclerotic process but were unable to document whether this could be linked to the number of lower extremity lesions and patient outcomes 17, 18.…”
Section: Discussionmentioning
confidence: 99%
“…More aggressive expression of atherosclerosis has been found in patients with distal versus aortoiliac disease and in patients in whom higher inflammation markers can be found 17, 18, 19. These studies suggested which concomitant factors could be associated with a more aggressive underlying atherosclerotic process but were unable to document whether this could be linked to the number of lower extremity lesions and patient outcomes 17, 18. Consequently, future work needs to verify whether having more lower extremity lesions is associated with a more aggressive underlying atherosclerotic process expressed by higher inflammation markers or undergoing multiple lower extremity revascularizations to better characterize PAD subpopulations that are at increased risk of an adverse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Smoking not only contributes to the incidence, but also is a significant predictor of progression of symptomatic PAD. 15 Smoking cessation may not reduce claudication symptoms but has been shown to reduce overall mortality and cardiovascular events. 16 …”
Section: Medical Therapy Tobacco Cessationmentioning
confidence: 99%
“…In this study, a positive correlation existed between ABI value and systolic blood pressure, diastolic blood pressure, and pulse pressure. In a longitudinal study of the general population, [16] among traditional risk factors, blood pressure was not an independent factor or significant predictor for ABI values. Vinuesa et al [17] described that in chronic kidney disease patients, low ABI value was correlated with low systolic blood pressure, low diastolic blood pressure, and high pulse pressure.…”
Section: Ankle-brachial Indexmentioning
confidence: 75%
“…Aboyans et al [16] recently identified risk factors contributing differentially to the progression of large-vessel peripheral vascular disease (LV-PAD) and small-vessel peripheral vascular disease (SV-PAD). Their study of the general population demonstrated that cigarette smoking, elevated lipid levels, and inflammation contribute to LV-PAD, and that diabetes was the only significant predictor of SV-PAD progression.…”
Section: Toe-brachial Indexmentioning
confidence: 99%